Governing University Living Labs for sustainability transformations: insights from 18 international case studies - Paris Hadfield; Darren Sharp; Jonas Pigeon; Rob Raven (Sustainability Science, 2025)
In recent years, scholarly debate has grown around a perceived gap between societal impact rhetoric and the support structures for interdisciplinary and applied research, education, and innovation in universities. University Living Labs (UniLLs) provide a window into this relationship as they transcend disciplinary boundaries and linear modes of engagement to enable real-world experimentation and learning in response to societal challenges such as sustainable development. However, few studies examine the institutional contexts in which UniLLs operate, thus limiting our understanding of universities’ capacity for sustainability experimentation. This study examines how the institutional structures, cultures, and practices of universities enable or constrain the governance of sustainability-oriented UniLLs. Our study is grounded in the practical work of organising and conducting UniLLs, drawing on interviews with 39 academics and practitioners involved in UniLLs at 18 universities in Australia, Brazil, Canada, Germany, France, The Netherlands, Singapore, the UK, and the USA. Our research findings demonstrate that (1) UniLLs are enabled by the institutionalisation of sustainable development agendas, and the relational and discursive work of key university staff. (2) UniLLs are often limited in scope and longevity by a project logic and work against entrenched academic and operational organising structures and corporate logics. (3) Some UniLLs overcome these barriers by leveraging institutional power and mobilising resources to embed UniLL governance in university-wide structures. We present practical enabling processes for institutionalising UniLLs in universities demonstrated by the cases and reflect on the university governance paradigm for advancing a transformative impact agenda.